2019
DOI: 10.3389/fimmu.2019.01218
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinical Manufacturing of IL-15 Activated Cytokine-Induced Killer (CIK) Cells

Abstract: Cytokine-induced killer (CIK) cells are an immunotherapeutic approach to combat relapse following allogeneic hematopoietic stem cell transplantation (HSCT) in acute leukemia or myelodysplastic syndrome (MDS) patients. Prompt and sequential administration of escalating cell doses improves the efficacy of CIK cell therapy without exacerbating graft vs. host disease (GVHD). This study addresses manufacturing-related issues and aimed to develop a time-, personal- and cost-saving good manufacturing process (GMP)-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…CD25 is the IL-2 receptor α-chain that interacts with the IL-2Rβ and IL-2Rγ subunits to form the high-affinity IL-2 receptor; 30 CD25 overexpression may facilitate the efficacy of cell therapies through the creation of an extracellular reservoir and recycling of IL-2, 31 and its upregulation correlates with the cytotoxic activity in NK and CIK cells. 32,33 Here we demonstrated that a CD25 upregulation occurred exclusively in the CD3 + CD56 + CD16 + subset and only in the presence of the antigen-specific mAb that could explain the enrichment of the CD3 + CD56 + CD16 + fraction within both primary and metastatic tumors when CTX was used.…”
Section: Discussionmentioning
confidence: 71%
“…CD25 is the IL-2 receptor α-chain that interacts with the IL-2Rβ and IL-2Rγ subunits to form the high-affinity IL-2 receptor; 30 CD25 overexpression may facilitate the efficacy of cell therapies through the creation of an extracellular reservoir and recycling of IL-2, 31 and its upregulation correlates with the cytotoxic activity in NK and CIK cells. 32,33 Here we demonstrated that a CD25 upregulation occurred exclusively in the CD3 + CD56 + CD16 + subset and only in the presence of the antigen-specific mAb that could explain the enrichment of the CD3 + CD56 + CD16 + fraction within both primary and metastatic tumors when CTX was used.…”
Section: Discussionmentioning
confidence: 71%
“…In previous work, we employed CIK cells after ex vivo activation with IL-15 for 10 days, which resulted in more rapid generation of CIK cells with stronger cytotoxicity compared to conventional CIK cells expanded in the absence of IL-15 over 3-4 weeks. (32,46,47). The main fraction in this short-term, IL-15-activated CIK cell culture is the CD3 + T cell population.…”
Section: Discussionmentioning
confidence: 99%
“… 59‐61 Several protocols for the generation of CIK cells have been reported, and typically involve the sequential incubation of peripheral blood lymphocytes with interferon (IFN)‐γ, anti‐CD3 mAb, and IL‐2 62 . The use of IL‐15 in the presence or absence of IL‐2 has also been shown to induce faster expansion of CIK cells to exhibit enhanced cytotoxicity, with the additional advantage of inducing fewer numbers of suppressive Treg cells 63,64 . CIK cells exhibit stronger cytolytic activity compared to lymphokine‐activated killer (LAK) cells, which are generated by incubation with interleukins.…”
Section: Cik Cellsmentioning
confidence: 99%
“…CIK cells exhibit stronger cytolytic activity compared to lymphokine‐activated killer (LAK) cells, which are generated by incubation with interleukins. Enhanced function of CIK cells relative to LAK cells has been attributed to a higher proliferative capacity and an increase in lytic units 64,65 …”
Section: Cik Cellsmentioning
confidence: 99%